A case control study investigating factors associated with high infant death in Saiha district of Mizoram, India bordering Myanmar. Issue 1 (December 2017) - Deb, Alok; Dutta, Shanta; Hnichho, Chhaihlo; Vanlalpeki, Mary; Phosa, Hli; Rakhu, Khaila; Fanai, Samuel; Chakrabarti, Manoj; Panda, Samiran
Abstract Background Infant mortality has dropped considerably in India over the last 5 years. A sharp contrast to this decline in national average of infant mortality is the rate recorded during 2014–2015 from the southernmost district of Saiha, Mizoram having a common international border with Myanmar. As this district specific rate (113 per 1000 live births) is 3 times higher compared to the national and state average, the present investigation was carried out to identify associated factors. Methods We examined secondary data made available by the national health mission, consulted with local community members and generated primary data through interviews. A case-control study design was followed. Mothers, who delivered a child during 2013–2015 and subsequently lost them due to infant death, formed the case group and controls were selected from same neighborhood as with case-mothers. The mother and child tracking system maintained by the district specific national health mission office was used for recruiting cases and controls. A total of 195 mothers were interviewed; 66 of them belonged to 'cases' and 129 were 'controls'. Results The mean age of the respondents was 27 years (median 27; SD ± 5; minimum 17 & maximum 44). In uni-variate analyses 'child delivery at home', 'low birth weight', 'non-attendance of school by mothers', 'completed standard of school education by mothers', 'both parents working', 'mothers receiving blood transfusion during last pregnancy', and 'fourth or more birth order during last pregnancy' were associated with infant deaths. Intriguingly, the number of dailykuhva (raw areca nut) intake during last pregnancy was significantly higher among case-mothers compared to controls. In conditional logistic regression, 'low birth weight' (adjusted OR (AOR) 14.7; 95% CI 2.1–101.8;p = 0.006), and 'consumption of 4 or morekuhva per day' (AOR 8; 95% CI 1.9–34.3;p = 0.005) were independently associated with infant-death-experiences. Conclusion The present investigation merits due attention from policy makers and health planners for immediate improvement in peri-natal and neonatal care services in the remote district of Saiha. Need for further research exploring socio-behavioural issues around areca nut consumption and effects of interventions to reduce areca nut intake on maternal and children health are underscored.